(untitled) (Modern education and development, 2024)
90 newborns with moderate to severe perinatal encephalopathy were examined. The analysis of the obtained data showed that the occurrence and development of the severity of perinatal encephalopathy depends on the presence and frequency of pathology of obstetric and gynecological history, the course of pregnancy and childbirth. Changes in the state of the central nervous system, particularly perinatal encephalopathy, may further affect the health of the child, and a late diagnosis may lead to a complicated and prolonged course of the disease. In connection with the above, 90 children were selected from the total number of newborns, and two groups were formed: Group I, consisting of 50 newborns with moderate perinatal encephalopathy, and Group II, consisting of 40 newborns with severe perinatal encephalopathy.